(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This research deals with measuring the levels of visual pollution in Al-Kazimiya district and its surroundings, which differ from other regions in terms of intensity and impact. Then the research addresses several solutions that will address the problem of visual pollution and reduce its environmental effects on the urban environment and the residents of the research area. The researchers note that there is a discrepancy in the manifestations of visual pollution between the areas of Al-Kazimiya district and its surroundings, and it also varies in terms of intensity and impact between regions, as they see that one of the manifestations of visual pollution intensifies in one region and weakens in another region, and because one of the ways to measure the intensity of visual pollution in a particular area (is the standard of public taste), the researchers formulated (10) questions that show the amount of visual pollution in each area of Al-Kazimiya and its surroundings, Through it, it is possible to draw a clear mental image of any manifestation of visual pollution.